Malrotation in infancy and childhood. Issue 2 (May 2016) - Arthur, Felicity; Carachi, Robert
Background and aims: The cardinal features of bilious vomiting and abdominal distension assist in the diagnosis of malrotation and volvulus, an often fatal condition in the neonate. When these symptoms are absent, however, diagnosis becomes trickier. In the older child, these classic symptoms are less likely to occur, or occur at a later stage, meaning these children suffer from a delay in diagnosis and consequently do poorer. There is a need, therefore, to identify the common presenting features in these older children in order to facilitate earlier diagnosis and improve outcomes. Methods: We reviewed the current literature (Appendix 1) and then undertook a retrospective study in our own department to explore the presenting complaint, time to diagnosis, intraoperative findings and outcome of all children over the age of 28 days who underwent a Ladd's procedure for malrotation at Royal Hospital for Sick Children, Glasgow (RHSC) between 1998 and 2014. Results: It was found that children between the ages of 28 days and 15 years are more likely to display signs and symptoms such as chronic abdominal pain and non-bilious vomiting. Their complication rate was found to be significant. Conclusion: Education surrounding the timely diagnosis of malrotation in the post-neonatal child is crucial.